BLUE GIANTS IN THE NEIGHBORHOOD OF ETA CARINAE - MUNCH, LUIS; MORGAN, WW (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1952)
We present the classification of 172 OB stars in the neighborhood of eta Carinae region. The data were obtained at the Tonantzintla Schmidt camera in spite of the low altitude of the field.
BOL OBS TONAN TACUB
Keywords: BLUE GIANTS, NEIGHBORHOOD, CARINAE; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS